Whole-genome sequencing identifies genetic diversity and adaptive signatures of hypoxia and ultraviolet radiation in Chinese chickens - Bello, S.F.; Terefe, E.; Ye, H.; Adeola, A.C.; Zhou, Z.; Jebessa, E.; Qi, L.; Ahmed, R.O.; Aloryi, K.D.; Ositanwosu, O.E.; Eludodun, S.J.; Zhang, Z.; et al. (Elsevier, 2026)
Introduction: Domestic chickens primarily descended from the wild red junglefowl, play a crucial role in global egg and meat production. China hosts diverse indigenous chicken populations that have adapted to various environmental conditions, including high-altitude with hypoxic and ultraviolet radiation stress.